GeoGebra-supported problem-based learning for in-service primary mathematics teachers’ 3D geometry understanding in a core primary teachers’ college in Uganda - Kirabo, Esther; Batiibwe, Marjorie Sarah Kabuye; Mbulankende, Julius Shopi; Lie, Johan (Frontiers in Education, 2025)
This study examined the impact of a GeoGebra-supported problem-based learning (GSPBL) intervention on in-service primary mathematics teachers’ understanding of three-dimensional (3D) geometry. Ninety-two teachers from a Core Primary Teachers’ College in Western Uganda participated, selected through purposive sampling. An explanatory sequential mixed methods design combined a pre-test-post-test control group experiment with instructional observations. A paired samples t-test showed that the experimental group’s post-test scores were, on average, 4.72 points higher than their pre-test scores (t = −6.565, df = 45, p < 0.001). An independent samples t-test (Welch’s correction) also revealed a significant post-test difference between groups, with the experimental group outperforming the control by 2.53 points [t = 3.780, df = 70.20, p < 0.001, 95% CI (1.20, 3.86)]. Observation data supported these results, indicating greater engagement, collaboration, visualization, and application of geometric concepts. The study concluded that GSPBL significantly improved teachers’ understanding of 3D geometry compared to traditional methods. The findings highlight the potential of technology-enhanced instruction to strengthen mathematics education. For in-service primary mathematics teachers, GSPBL offers an effective approach to developing mathematics conceptual understanding. For researchers, it provides evidence of the pedagogical value of GeoGebra as a dynamic geometry tool, and for policymakers, it underscores the need to integrate GSPBL into teacher education, enhance digital infrastructure, and support continuous professional development in technology-supported pedagogy.